MENDADAK E-LEARNING: STUDI KUALITATIF MAHASASISWA PERGURUAN TINGGI SELAMA MASA PANDEMI COVID-19: SUDDEN E-LEARNING: A QUALITATIVE STUDY OF UNIVERSITY STUDENTS DURING THE COVID-19 PANDEMIC - Mazhabi, Zobi; Amirudin, Yoyok (Universitas Islam Malang, 2021)
The Covid 19 pandemic brings significant distruption to education, carrying out new challenge for education, and making alot of educational institutions stake holders becoming stressfull. This study aimed at analyzing the college students perception on shifting off line learning to online learning during Covid 19 pandemic . This study was conducted qualitatively through the implemetation of pre-structure interview by involving 35 student who spread in two different kinds of faculties, six different majors, and selected from 245 college students. The Interview was conducted to gather the data and to gain boundaries of direct perception and experiences belong to college students who became one part of primary element to this issue. It also was conducted based on the guidelines designed by the researchers and the data gathered analyzed with content analysis method in term of descriptive content analysis, inferential content analysis, psychometric content analysis, predictive content analysis. The findings of this research showed that on-line learning during Covid-19 pandemic contributed both of positive experience and negative experience to the students in term of physical element, psychological element, and cognitive element. The finding lead to the conclusion that, the lectures need to pretend to the opportunities, weaknesses, strength, and threats of this shifting issues in order to obtain the possible action for better development of the on-line learning system.